2009
DOI: 10.5713/ajas.2009.80216
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Insulin-like Growth Factor System in Breast Muscle during Embryonic and Postnatal Development in Langshan and Arbor Acres Chickens Subjected to Different Feeding Regimens

Abstract: Nutrient availability may control muscle growth directly and indirectly through its influence on regulatory factors. We * This work was supported by the Three Renewal Projects Foundation of Jiangsu Agriculture, China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 63 publications
2
7
1
Order By: Relevance
“…In our study, the duck breast muscle had the highest IGF-II mRNA at week 1 and then declined to a relatively lower level. Lu et al (2009) have also reported that IGF-II mRNA expression decreased progressively from postnatal day 0 to postnatal day 42 in chickens, which is consistent with the results of other reports (Spencer et al, 1995(Spencer et al, , 1996Richards et al, 2005). All of these findings suggest that IGF-II does not regulate growth after the postnatal period in birds.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In our study, the duck breast muscle had the highest IGF-II mRNA at week 1 and then declined to a relatively lower level. Lu et al (2009) have also reported that IGF-II mRNA expression decreased progressively from postnatal day 0 to postnatal day 42 in chickens, which is consistent with the results of other reports (Spencer et al, 1995(Spencer et al, , 1996Richards et al, 2005). All of these findings suggest that IGF-II does not regulate growth after the postnatal period in birds.…”
Section: Discussionsupporting
confidence: 90%
“…At present, several studies have reported positive or negative correlations between circulating IGF-I concentration and body growth in chickens (Hwa et al, 1998;Beccavin et al, 2001;Lu et al, 2009). Conlon and Kita (2002) have suggested that IGF-I infusion would increase muscle protein degradation as well as protein synthesis in fasted chicks.…”
Section: A Correlation Exists Between Muscle Tissue Weight and Igf Gementioning
confidence: 99%
See 3 more Smart Citations